Improvement of the bending behavior of a flexible riser: Part ii – hysteretic modeling of bending stiffness in global dynamic analysis. (August 2020) - Du Kim, Jeong; Jang, Beom-Seon; Yun, Ran-Hui; Jeong, Hyeon-Su
Highlights: This paper proposes new global dynamic analysis methods for flexible risers with consideration of interlayer interactions. This paper suggest a multi hysteresis modeling method which considers the variation of axisymmetric loads and shear deformation effects. A comprehensive investigation on the dynamic responses of flexible risers is carried out using the suggested multi hysteresis modeling method. The interlayer interaction is found to have a significant impact on the global responses and fatigue damage. A partial hysteresis method is additionally introduced to improve the modeling and computational efficiency of global dynamic analysis. Abstract: Flexible risers have been widely utilized for the transfer of oil and gas products from the well to the production unit. Continuous interactions of tensile armor layers and anti-friction tapes trigger the slippage of helical wires and a highly nonlinear hysteric behavior in bending. For the precise prediction of the bending behavior of flexible risers, Part I of this series of papers proposed a new analytical model that successfully models the interlayer interaction. In this paper, Part II, the proposed analytical model is extended to the global domain of riser configurations; that is to say, a Multi-Hysteresis Modeling (MHM) method is proposed The proposed method employs accurate and realistic bending hysteresis curves with consideration of shear deformation and axisymmetric loads. Based on the proposed method, three comparative studies are performed to investigate the effects of interlayer interaction. As a result, the interlayer interaction is found to have a considerable impact on the fatigue damage of flexible risers. For a practical global dynamic analysis procedure, this paper also introduces a partial hysteresis modeling (PHM) method, by which only a small number of local regions are modeled with bending hysteresis curves.